2018
DOI: 10.3390/catal8120581
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Carbon Dioxide to Methanol over Copper Based Zeolitic Imidazolate Framework-8: A New Generation Photocatalyst

Abstract: The efficient reduction of CO2 into valuable products such as methanol, over metal-organic frameworks (MOFs) based catalyst, has received much attention. The photocatalytic reduction is considered the most economical method due to the utilization of solar energy. In this study, Copper (II)/Zeolitic Imidazolate Framework-8 (Cu/ZIF-8) catalysts were synthesized via a hydrothermal method for photocatalytic reduction of CO2 to methanol. The synthesized catalysts were characterized by X-ray Photoelectron Spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…For example, ZIF-8 has bandgap of 4.3 eV [74] . Thus, it shows zero rate of photocatalytic reduction of CO2 [323][324][325] . The common applications of ZIF for photo-reduction are co-catalysts or support (Table 5) [326,327] .…”
Section: 5photocatalytic Reduction Of Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ZIF-8 has bandgap of 4.3 eV [74] . Thus, it shows zero rate of photocatalytic reduction of CO2 [323][324][325] . The common applications of ZIF for photo-reduction are co-catalysts or support (Table 5) [326,327] .…”
Section: 5photocatalytic Reduction Of Co2mentioning
confidence: 99%
“…Au@PtAg/ZIF-8 [329] , Ag@ZIF-8@g-C3N4 [330] , CdS/ZIF-8 [331] , CdS@ZIF-67 [332] , CdSe@ZIF-8 [333] , ZnO/ZIF-8 [325,334] , ZnO@Pt/ZIF-8 [335] , ZnO/Au@ZIF-8 [336] , Au@ZIF-67 [337] , TiO2/ZIF-8 [338,339] , TiO2/Co-ZIF-90 [340] , Cu/ZIF-8 [323] , Zn2GeO4/ZIF-8 [324] , and WO3/CsPbBr3/ZIF-67 [341] (Table 5). ZIFs materials were also used as precursor for the synthesis of metal oxide embedded into carbon such as ZIF-67/MIL-125-derived Co3O4/TiO2 (Figure 17) [342][215] .…”
Section: 5photocatalytic Reduction Of Co2mentioning
confidence: 99%
“…Catalytic activity and optimization study of catalysts were tested in an optical fiber photocatalytic reactor. The detailed set up of the photocatalytic study has been reported in previous work [43]. The schematic representation of photocatalytic reduction is shown in Figure A2.…”
Section: Photocatalytic Studymentioning
confidence: 99%
“…The incorporation of metal ions into the MOFs will increase the photocatalytic performance of CO 2 reduction to respective products, rendered from the enhanced photogenerated charge carrier and separation with apt minimum decay; thus, carefully engineered Cu-based MOFs are effective in long-lived electron generation and substrate reduction. Goyal et al provided an orthorhombic structured NP of MOF from Copper (II)/Zeolitic Imidazolate Framework-8 (2Cu/ZIF-8N2) photocatalyst in ammonium hydroxide concentration via hydrothermal process used for CO 2 conversion to methanol; the as-synthesized MOF had a bandgap of 1.75 eV, VB (0.72 V vs. NHE), and CB (−1.02 V vs. NHE @ pH = 7), implying lower VB than that of ZIF-8 (2.41 V vs. NHE), meaning the oxidation reaction took place in ZIF-8 [220]. On the other hand, the more negative-value CB of synthesized MOF to the CO 2 to MeOH potential (−0.38 V) affirmed this MOF's reduction potential with apropos metal loading.…”
Section: Cu-based Mofmentioning
confidence: 99%